Potential Challenges of the Extraction of Carotenoids and Fatty Acids from Pequi (Caryocar brasiliense) Oil - Camila Rodrigues Carneiro; Adamu Muhammad Alhaji; César Augusto Sodré da Silva; Rita de Cássia Superbi de Sousa; Simone Monteiro; Jane Sélia dos Reis Coimbra (Foods, 2023)
Pequi is a natural source of bioactive compounds with wide versatility for fresh or processed fruit consumption, but it is still little explored economically. Functional foods are the subject of diverse scientific research since, in addition to being nourishing, they contain bioactive compounds capable of promoting several benefits to the human body. Pequi is a fruit species native to the Brazilian Cerrado, which is rich in oil and has components with a high nutritional value, such as unsaturated fatty acids (omega-3, omega-6, EPA, and DHA), antioxidants (carotenoids and phenolic compounds), and vitamins. Therefore, the present narrative review aims to compile and critically evaluate the methods used to extract oil from the pulp and almonds of pequi and describes the carotenoid separation from the oil because carotenoids are natural pigments of great interest in the pharmaceutical and food industries. It is emphasized that the main challenges linked to bioactive compound extraction are their susceptibility to degradation in the processing and storage stages of pequi and its derived products.